MIGRASI KURIKULUM 2013 MENUJU KURIKULUM MERDEKA - Ahmad Syaddad; M. Hanif Satria Budi; Aniqutus Shofwa (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Curriculum implementation in education units is a must. The school curriculum must be diversified with existing government student programs. This aims to harmonize with the applicable laws. As currently the Indonesian state curriculum is an independent curriculum, where existing schools are required to implement this curriculum, and leave the previous curriculum, namely the 2013 curriculum. As in SMA Negeri 2 Pare Kediri, this school has implemented an independent curriculum and abandoned the 2013 curriculum, the 2013 curriculum was applied last to graduates in 2024. The purpose of this study is to describe the process of changing the independent curriculum as a complement to the 2013 curriculum for students at SMA Negeri 2 Pare Kediri. This research uses a descriptive analysis method using a qualitative approach. Researchers collected data through interview techniques, observation and literature study to complement the statements from the interview results. The results of the study found that there were changes during the implementation of the independent curriculum on the students. The transition from the 2013 curriculum to the independent curriculum did not experience many obstacles because the students were more enthusiastic in the learning process and the teachers were also enthusiastic in attending teacher special education.